2017
DOI: 10.1016/j.biopsych.2016.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Orexins Mediate Sex Differences in the Stress Response and in Cognitive Flexibility

Abstract: BACKGROUND Women are twice as likely as men to suffer from stress-related psychiatric disorders. However, the biological basis of these sex differences is poorly understood. Orexins are altered in anxious and depressed patients. Using a rat model of repeated stress, we asked whether orexins contribute to sex differences in outcomes relevant to stress-related psychiatric diseases. METHODS Behavioral, neural, and endocrinal habituation to repeated restraint stress and subsequent cognitive flexibility was exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
113
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(122 citation statements)
references
References 41 publications
8
113
0
1
Order By: Relevance
“…Our previous work has revealed that the neuropeptides orexins mediate sex differences in habituation to repeated stress (Grafe et al, 2017). Specifically, elevated levels of orexins in female rats impair habituation to repeated restraint stress.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous work has revealed that the neuropeptides orexins mediate sex differences in habituation to repeated stress (Grafe et al, 2017). Specifically, elevated levels of orexins in female rats impair habituation to repeated restraint stress.…”
Section: Discussionmentioning
confidence: 99%
“…We aimed to determine if there were observable structural differences in these putative orexinergic dendrites in males compared with females in basal conditions, and if repeated restraint stress affects any sex differences observed. As we observed greater prepro-orexin mRNA and activation in basal, non-stressed females (Grafe et al, 2017), we hypothesized that there would be more complex dendritic morphology and a greater number of spines in control females compared with males. This would be reflective of more excitable orexin cells in females.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Studies of humans (Shields, Trainor, Lam, & Yonelinas, 2016) and mice (Laredo et al, 2015) have found that cognitive flexibility in males was more significantly impaired following a stressor, although one recent study found that female rats were more affected (Grafe, Cornfeld, Luz, Valentino, & Bhatnagar, 2017). Sex-differences in cognitive performance between men and women are also reported in pathological conditions.…”
Section: Exercise Sex and Age Effects On Cognitive Flexibility And mentioning
confidence: 99%